Modelled cost-effectiveness analysis of the Support and Treatment After Replacement (STAR) care pathway for chronic pain after total knee replacement compared with usual care - Cole, S; Noble, S; Gooberman-Hill, R; Pinedo Villanueva, R (BioMed Central, 2024)
Background The aim of the study was to estimate the long-term cost-effectiveness of the Support and Treatment After Replacement (STAR) care pathway for chronic pain after total knee replacement compared with usual postoperative care. Methods Study design: A decision-analytic (cohort Markov) model was used for the simulation with time dependent annual transition probabilities and a time horizon of five years. Setting: Patients treated by National Health Service (NHS) hospitals in England and Wales. Study population: Adults classified as having chronic pain three months after undergoing a total knee replacement. Intervention: The STAR care pathway following a total knee replacement. Comparator: Usual postoperative care following a total knee replacement. Perspective: The study was undertaken from the perspective of the NHS. Outcome measures: Quality-adjusted life years and healthcare costs. Discounting: A rate of 3.5% for both costs and health utility.